Status, Importance and Major Issues in Water Source in Watershed of Chitwan, Nepal - Shrestha, Prerana; Manandhar, Bikram; Dhungana, Nabin; Rajbhandari, Sujan (FORESTRY: Journal of Institute of Forestry, Nepal, 2020)
Khageri Khola sub-watershed of the Chitwan district is stressed by climate change and is facing changes in its water source. The main objective of this study was to assess the status of water sources, their importance, water source issues, and distribution of water sources as well as to suggest appropriate conservation and management measures. Various participatory tools such as household interviews, focus group discussions and stakeholder’s consultations were used. In total, 56 water sources were identified in eight micro-watersheds in Khageri Khola sub-watershed. The overall water sources were found decreasing with moderate (43%) to insufficient (32%) amount of water available for drinking. People meet their current water demand through tap water (43%) and tube wells/wells (38%). Conservation and management measures such as tree plantation, solar planning (solar power for water pumping system) for wildlife, construction of water tanks and bamboo plantation have been adopted. Hence, upstream soil erosion should be reduced to save downstream sources from flash floods by emphasizing land use planning. Regular observation, capital funding for water sources and catchment conservation and awareness programs are further required to minimize the possible risks on water sources.